Kaizen events: an assessment of their impact on the socio-technical system of a Mexican company - Cavazos-Arroyo, Judith (2018)
Objective: This work assesses how the abilities developed during Kaizen events impact three variables: employees’ attitude, motivation, and impact on the work area. Materials and methods: We used a quantitative, explanatory and cross-design approach in a Mexican company where Kaizen events occur on a daily basis. As a technique of statistical analysis, we used structural equation modeling employing Partial Least Squares (PLS). Results and discussion: We found that the abilities developed during Kaizen events have a significant positive influence on the three variables studied. Additionally, we found that motivation positively influences the impact on the work area. Finally, we discovered a relationship between the employees’ attitude toward their work and their motivation. That relationship is part of the synergy that begins with the abilities developed during Kaizen events and concludes with an impact on the work area. Conclusions: The abilities developed during Kaizen events influence employees’ attitude toward their work, motivation and work area impact. Likewise, the attitude toward work affects motivation, and this variable positively affects the work area. We recommend that future studies of Kaizen environments analyze whether the employees’ attitude toward work affects the impact on the work area and whether the studied variables influence the organizations’ productivity and profitability.